Management of assessment tools for children's writing - Lee, Irene Lay Lan. (2008)
Administrators in pre-schools face challenging tasks as educational leaders and accountability agents. As administrators, they are accountable to the various stakeholders for the teachers and children's performance. Hence, it is necessary for them to be equipped with effective and developmentally-appropriate assessment tools.